QR-code based E-wallet System using Android platform - Kayalvily, Tabianan; Siti Qalillah Adawiah, Abdul Rahman; Deshinta, Arrova Dewi (INTI International University, 2019)
Currently, in order to make payment or purchase an item, the INTI community needs to pay with physical cash. Since they use physical cash, it means they are required to carry their wallet/purses around, and there is a chance that they may lose it, thus, money is lost/stolen. Furthermore, they need to make frequent trips to Automated Teller Machines (ATM). The E-wallet can provide a safer platform to make payments and purchase items, thus eliminating the need to carry cash around. E-wallet system is a kind of electronic card which is utilized for exchanges made online through a PC or a cell phone. Its utility is same as a credit card. An E-wallet should be connected with the person's bank account to make payments. This paper aims to study about E-wallet system and how it can be implemented into INTI community. The objectives of this project was to study about the current methods of making payments in INTI while investigating how E-wallet system can be used to enhance payment experience and safety for INTI community. After that, to design and implement a mobile application which is QR-code based and lastly, to conduct testing for the proposed system to ensure the accuracy. For this project, the author primarily used Android Studio as the software to develop the system and Firebase Real-Time database to store and retrieve users’ information. The project has demonstrated the basic needs of an E-wallet System and showed that it is possible to be implemented in INTI